The Problem of Excessive Commercial Bank Earnings - Seligman, Harold L. (Quarterly Journal of Economics, 1946)
Changes in composition of commercial bank assets and earnings, 365. — The problem posed by these developments, 368. — Possible action by the banks themselves, 369. — Inadequacy of such measures, 373. — The Economist's proposal, 374. — Proposals for Government action: nationalization, 376; special taxes on banks, 378; new reserve requirements, 380; special Treasury obligations, 382; restricting types of Government securities held, 385. — Necessity of some action, 388.